Pengembangan Media Pembelajaran Berbasis Powerpoint Interaktif pada Materi Marketing Mix (7P) untuk Siswa SMK Bisnis Ritel - Fahmawati Siti Zubaedah; Nadya Fadillah Fidhyallah; Rizka Zakiah (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to develop interactive PowerPoint-based learning media on Marketing Mix (7P) material for retail business vocational high school students and determine the feasibility level of the developed media. This study used the Research and Development (R&D) method with the ADDIE development model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The resulting product is an interactive PowerPoint learning media equipped with learning materials, learning videos, interactive quizzes, Marketing Mix (7P) simulations, learning evaluations, and navigation that makes it easier for students to learn independently or with the teacher. Feasibility testing was carried out by material experts, media experts, and instructional design experts, as well as tested on students through small group and large group tests. The results showed that the developed learning media obtained material expert validation scores of 94%, media experts 96%, and instructional design experts 86%, all of which were in the Very Feasible category. The results of trials on students showed a feasibility percentage of 88% in the small group and 99% in the large group with the Very Feasible category. Overall, the interactive PowerPoint-based learning media obtained an average feasibility of 93% in the Very Feasible category. These results indicate that the developed media is feasible to use as a learning medium on Marketing Mix (7P) material, able to increase student engagement, provide a more interactive learning experience, and help students understand marketing concepts more effectively.